Strengthening Religious Moderation To Promote Social Cohesion And Peaceful Coexistence In Multicultural Societies - Muh ibnu sholeh; Siti Fatinnah Binti Ab Rahman (MUNIF: International Journal of Religion Moderation, 2025)
In today’s increasingly interconnected and multicultural world, religious diversity presents both opportunities and challenges to social cohesion. Religious moderation emerges as a critical approach to fostering mutual respect, tolerance, and peaceful coexistence among communities with differing beliefs and practices. This study explores strategies and best practices in implementing religious moderation as a tool to strengthen intergroup harmony and reduce religion-based conflicts in pluralistic societies. Using a qualitative descriptive-analytical method supported by literature reviews, policy analyses, and case studies, this research identifies three key dimensions: (1) educational approaches that integrate moderation values into formal and informal curricula, (2) community-based initiatives that facilitate interfaith dialogue and collaborative problem-solving, and (3) government-led policies and legal frameworks that support inclusivity and protect minority rights. The findings reveal that societies adopting a holistic, multi-stakeholder approach to religious moderation demonstrate higher levels of trust, reduced polarization, and sustainable peace. This study highlights the need for cross-sector collaboration between policymakers, educators, religious leaders, and civil society actors to build a culture of mutual understanding and respect.